2015
DOI: 10.1590/0102-33062014abb3697
|View full text |Cite
|
Sign up to set email alerts
|

Species composition, diversity, and vegetation structure in a gallery forest-cerrado sensu stricto transition zone in eastern Mato Grosso, Brazil

Abstract: We investigated the existence of an ecotone in the species composition, diversity and vegetation structure in the transition between gallery forest and cerrado sensu stricto in central Brazil. We tested two hypotheses: 1) a ecotone can be found between gallery forest and cerrado; 2) a gradient exists in the species composition of the cerrado. We established three parallel transects of 5 m × 350 m running between gallery forest and cerrado, which were divided into subplots of 5 m × 10 m, perpendicular to the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…pseudotaxus, as demonstrated by the Indicator Species Analysis. Local site-specific environmental characteristics such as relief, topography, and physicochemical soil properties may play a secondary role, as demonstrated in other studies in the woodlands of southern Africa and savanna biome of South America [87,88].…”
Section: Principal Coordinates Similarity and Indicator Speciesmentioning
confidence: 73%
“…pseudotaxus, as demonstrated by the Indicator Species Analysis. Local site-specific environmental characteristics such as relief, topography, and physicochemical soil properties may play a secondary role, as demonstrated in other studies in the woodlands of southern Africa and savanna biome of South America [87,88].…”
Section: Principal Coordinates Similarity and Indicator Speciesmentioning
confidence: 73%
“…Em torno de 65% das 30 espécies registradas com maior VI no presente estudo são comumente encontradas em áreas de cerrado sentido restrito sobre solos profundos (RATTER et al, 2003;MENDONÇA et al, 2008;LENZA et al, 2015). Dentre essas espécies mais importantes (VI), merecem destaque Caryocar brasiliense, Curatella americana, Dimorphandra mollis, Myrcia bella e Qualea grandiflora.…”
Section: Discussionunclassified
“…Our analyzes also showed that the floodplains differ from the others in both cluster analysis and ordination. The influence of soil and river basin moisture is evident, showing that the floristic variation of the Transition is strongly related to local variations, and closer areas tend to be more similar to each other than to areas geographically close to river basins (Lenza et al 2015;Morandi et al 2016). Another remarkable pattern was the fact that the forested savannas (both dystrophic and mesotrophic ones) presented a greater floristic similarity with the typical savannas.…”
Section: Drivers Of Floristic Variation In Biogeographic Transitions:mentioning
confidence: 96%